2021
DOI: 10.1186/s41606-020-00054-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiometabolic health and objectively-measured, free-living sleep parameters: a pilot study in a rural African setting

Abstract: Objectives To investigate the relationship between objectively-measured, free-living sleep quantity and quality, and cardiometabolic health, in a rural African setting in 139 adults (≥40 years, female: n = 99, male: n = 40). Wrist-mounted, tri-axial accelerometry data was collected over 9 days. Measures of sleep quantity and quality, and physical activity were extracted from valid minute-by-minute data. Self-reported data included behavioural, health and socio-demographic variables. Biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, in a demographic surveillance study done in South Africa using actigraphy sleep measures, it was found that insufficient and fragmented sleep were significantly associated with poor cardiometabolic health outcomes ( 14 ) ( Table 1 ). Another pilot study in a rural setting in South Africa using the same sleep measurements found that objectively measured short sleep duration was significantly associated with HOMA-IR and showed a linear relationship with type-2 diabetes mellitus ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a demographic surveillance study done in South Africa using actigraphy sleep measures, it was found that insufficient and fragmented sleep were significantly associated with poor cardiometabolic health outcomes ( 14 ) ( Table 1 ). Another pilot study in a rural setting in South Africa using the same sleep measurements found that objectively measured short sleep duration was significantly associated with HOMA-IR and showed a linear relationship with type-2 diabetes mellitus ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Cook et al. found a significant non-linear (U-shaped) association between short sleep duration and JIS-MetS risk (p = 0.0308) ( Table 1 ) ( 16 ). The findings of this study are consistent with the study conducted by Rae et al.…”
Section: Main Textmentioning
confidence: 99%